Intrathecal synthesis of antibodies to HTLV-III in patients without AIDS or AIDS related complex. Issue 6530 (10th May 1986) - Goudsmit, J; Wolters, E C; Bakker, M; Smit, L; Van der Noordaa, J; Hische, E A; Tutuarima, J A; Van der Helm, H J
Abstract : De novo synthesis in the central nervous system of IgG antibodies to human T cell lymphotropic virus type III (HTLV-III) (lymphadenopathy associated virus) was shown in seven of 10 seropositive men who had syphilis but not the acquired immune deficiency syndrome (AIDS) or AIDS related complex. None of these men showed neurological symptoms when the serum and cerebrospinal fluid were collected. Pleocytosis was present in all 10. Of the seven men who showed evidence of intrathecal synthesis of antibodies, five had increased total concentrations of IgG and four had oligoclonal IgG bands in their cerebrospinal fluid. Oligoclonal bands were also present in one man who did not have any antibodies. Longitudinal study of one man showed that seroconversion preceded intrathecal synthesis of antibody specific to HTLV-III. The appearance of antibody in the cerebrospinal fluid was accompanied by a transient rise in mononuclear cell count and the appearance of oligoclonal bands. The presence of clones of B cells specific to HTLV-III in the central nervous system of these patients without persisting neurological symptoms suggests that HTLV-III enters the central nervous system in the early stages of infection.